2017
DOI: 10.4314/tjpr.v16i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Tangeretin sensitises human lung cancer cells to TRAILinduced apoptosis via ROS-JNK/ERK-CHOP pathwaymediated up-regulation of death receptor 5

Abstract: Purpose: To investigate the efficacy of tangeretin, a bioactive flavonoid, as an enhancer of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis in human lung cancer cells (H1299 and H1975).Methods: H1299 and H1975 cells were exposed to tangeretin (25, 50, or survivin, xIAP,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Additionally, tangertin in combination with TRIAL in H1299 and H1975 cells downregulated anti-apoptotic Bcl-2, Bcl-xL, survivin, x-IAP, c-IAP1, and c-IAP2 and elevated expression of pro-apoptotic Bax and caspases-3, -8, and -9. In addition to a significant increase in expression of DR 4 and 5, induction of ER stress was mediated via upregulation of CHOP and elevation of ROS [161].…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Additionally, tangertin in combination with TRIAL in H1299 and H1975 cells downregulated anti-apoptotic Bcl-2, Bcl-xL, survivin, x-IAP, c-IAP1, and c-IAP2 and elevated expression of pro-apoptotic Bax and caspases-3, -8, and -9. In addition to a significant increase in expression of DR 4 and 5, induction of ER stress was mediated via upregulation of CHOP and elevation of ROS [161].…”
Section: Phytochemicalsmentioning
confidence: 99%
“…As mentioned before, miRNA could bind to 3'-UTR of target mRNA to induce translational repression. There are target regions called "seed regions", which refer to the 7 nucleotides at 2 to 8 at the 5′ end of miRNA [12]. The "seed region" is the key sequence to recognize the target of miRNAs [12].…”
Section: Discussionmentioning
confidence: 99%
“…There are target regions called "seed regions", which refer to the 7 nucleotides at 2 to 8 at the 5′ end of miRNA [12]. The "seed region" is the key sequence to recognize the target of miRNAs [12]. The prediction results in this study from TargetScan indicated that there was a complementary sequence between 3'-UTR of CAMKK2 and 2 to 8 at the 5′ end of miR-378a-5p in compliance with Watson-Crick match [24], suggesting that calmodulin-dependent protein kinase kinase-2 was the direct target of miR-378a-5p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small noncoding microRNAs (miRNAs) have inhibitory effects on protein translation by directly targeting the 3′-untranslated region (3′-UTR) of mRNAs [4]. Many studies revealed that miRNAs were involved in the regulation of innate and adaptive immune responses [4]. For example, 66 aberrant miRNAs were identified using miRNA microarray chip analysis of renal biopsies of LN patients [5].…”
Section: Introductionmentioning
confidence: 99%